Mission Overview and Initial Observation Results of the X-Ray Pulsar Navigation-I Satellite - Xinyuan Zhang; Ping Shuai; Liangwei Huang; Shaolong Chen; Lihong Xu (International Journal of Aerospace Engineering)
The newly launched X-ray pulsar navigation-I (XPNAV-1) is an experimental satellite of China that is designed for X-ray pulsar observation. This paper presents the initial observation results and aims to recover the Crab pulsar’s pulse profile to verify the X-ray instrument’s capability of observing pulsars in space. With the grazing-incidence focusing type instrument working at the soft X-ray band (0.5–10 keV), up to 162 segments of observations of the Crab pulsar are fulfilled, and more than 5 million X-ray events are recorded. Arrival times of photons are corrected to the solar system barycentre, and the 33 ms pulse period is sought out for Crab. Epoch folding of all the corrected photon times generates the refined pulse profile of Crab. The characteristic two-peak profile proves that the Crab pulsar has been clearly seen, so that the conclusion is made that XPNAV-1’s goal of being capable of observing pulsars is achieved.